2019
DOI: 10.7717/peerj.7265
|View full text |Cite
|
Sign up to set email alerts
|

Towards optimized viral metagenomes for double-stranded and single-stranded DNA viruses from challenging soils

Abstract: Soils impact global carbon cycling and their resident microbes are critical to their biogeochemical processing and ecosystem outputs. Based on studies in marine systems, viruses infecting soil microbes likely modulate host activities via mortality, horizontal gene transfer, and metabolic control. However, their roles remain largely unexplored due to technical challenges with separating, isolating, and extracting DNA from viruses in soils. Some of these challenges have been overcome by using whole genome amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 91 publications
0
72
1
Order By: Relevance
“…Consequently, to desorb virions, various chemical reagents with different charges and physical methods are employed [5]. Virus desorption methods in particular should be tailored to specific soil types [35,[153][154][155]. We therefore first suggest characterizing a soil to understand its anion/cation-exchange capacity (a measure of how many ions can be retained on soil particle surfaces [156]) and, separately, the diversity of the associated microbial community (e.g., via 16S rRNA gene surveys).…”
Section: The Challenge Of Separating Virions From Soilsmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, to desorb virions, various chemical reagents with different charges and physical methods are employed [5]. Virus desorption methods in particular should be tailored to specific soil types [35,[153][154][155]. We therefore first suggest characterizing a soil to understand its anion/cation-exchange capacity (a measure of how many ions can be retained on soil particle surfaces [156]) and, separately, the diversity of the associated microbial community (e.g., via 16S rRNA gene surveys).…”
Section: The Challenge Of Separating Virions From Soilsmentioning
confidence: 99%
“…Presumably this technique would not work to remove all niVLPs, because, as noted, a VLP could become non-infectious due to defects in genes or nucleic acid structure rather than due to pores in capsids (Section 4.1). Nevertheless, PMA treatment is still useful, as one environmental metagenomic study, in which samples were collected from a clean-room floor, found that removal of relic DNA allowed detection of microbes and viruses that were not otherwise detected due to their low prevalence relative to that of relic DNA [155]. Once PMA treatment is performed, or any method of eDNA removal, qPCR can be used with 16S or 18S rRNA gene primers [184] to check to see if microbial DNA is still present in a virome, either because microbial relic DNA was not removed during PMA treatment or microbial DNA remained within intact ultrasmall microbial cells (Section 4.3).…”
Section: Removing Edna From Environmental Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…For identification and classification of viral contigs, we used MetaPhinder (v2.1, Jurtz et al, 2016) through the web interface hosted at the Center for Genomic Epidemiology at the Danish Technical University (DTU). Additionally, we queried the Viral_rep and Phage_F domains of the PFAM database using hmmsearch (HMMER v3, Eddy, 2011) to identify ssDNA contigs (Trubl et al, 2019).…”
Section: Bioinformatic Analysesmentioning
confidence: 99%